2020
DOI: 10.3390/v12121474
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated African Swine Fever Viruses as Ideal Tools to Dissect the Mechanisms Involved in Cross-Protection

Abstract: African swine fever (ASF) has become the major threat for the global swine industry. Furthermore, the epidemiological situation of African swine fever virus (ASFV) in some endemic regions of Sub-Saharan Africa is worse than ever, with multiple virus strains and genotypes currently circulating in a given area. Despite the recent advances on ASF vaccine development, there are no commercial vaccines yet, and most of the promising vaccine prototypes available today have been specifically designed to fight the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 36 publications
(25 reference statements)
0
32
0
4
Order By: Relevance
“…On an applied note, the observation of molecular divergence between Tanzania/Rukwa/2017/1 and Georgia 2007/1, together with the viruses recently derived from the latter, suggests that live attenuated vaccines derived from Georgia/2007/1 may not always cross-protect against ASFV genotypes derived from different regions of Africa, as it has been observed for phylogenetically distant ASFV strains within the ASFV p72 genotypes 46 .…”
Section: Discussionmentioning
confidence: 93%
“…On an applied note, the observation of molecular divergence between Tanzania/Rukwa/2017/1 and Georgia 2007/1, together with the viruses recently derived from the latter, suggests that live attenuated vaccines derived from Georgia/2007/1 may not always cross-protect against ASFV genotypes derived from different regions of Africa, as it has been observed for phylogenetically distant ASFV strains within the ASFV p72 genotypes 46 .…”
Section: Discussionmentioning
confidence: 93%
“…ASFV is a swine virus for which no vaccine has been approved yet. The development of attenuated vaccines in which specific immunomodulators are removed is a promising approach [ 15 , 16 ]. Work with other large DNA viruses has demonstrated that the removal of NF-κB inhibitors enhances the development of effector and memory T cell responses, and provides safer and yet more immunogenic vaccine vectors [ 46 , 47 , 48 ], although multiple deletions have been shown to reduce immunogenicity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…ASFV produces a deadly infection of swine that is spreading in three continents (Asia, Europe and Africa) with high economic burden. At present, there is not a commercial vaccine available, although live attenuated vaccines are being developed by deletion of genes related to the viral manipulation of the immune system [ 15 , 16 ]. Hence, a better understanding of how ASFV evades host immune responses has the potential to impact in the rational design of these vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Even though most of the times protection is limited to homologous protection [ 13 , 16 , 17 ], LAVs have become essential tools to confirm the protective role of innate [ 35 , 36 , 37 , 38 ] and adaptive immune responses, with both humoral response [ 39 , 40 , 41 ] and ASFV-specific CD8 + T-cells [ 21 ] playing crucial roles in protection. In this regard, recombinant LAVs are the most advanced candidates against the pandemic virus [ 14 , 15 , 16 , 17 ]. Although still pending approval from the authorized governmental agencies, LAVs candidates should contribute in the near future to control ASF in endemic areas and in emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the latest blueprint published by the European Commission, live attenuated viruses (LAVs) are the most plausible ASF-vaccine option in the short term [ 10 ]. The only data indicating protection from challenge infection available today against the pandemic ASFV strain, currently circulating in Asia and Europe, come from the use of naturally attenuated virus strains [ 11 , 12 ] or recombinant LAVs [ 13 , 14 , 15 , 16 , 17 , 18 ]. Despite their protective abilities, LAVs have to improve their safety and DIVA capabilities to be commercially viable in ASF-free areas.…”
Section: Introductionmentioning
confidence: 99%